The Reason of Jakarta People in Determining The Choice of Politics in Election 2014 - Tukina, Tukina (Bina Nusantara University, 2016)
The purpose of this research was to find out the reasons Jakarta’s residents in determining the political choice in election 2014. This research was conducted with descriptive qualitative method, by conducting in-depth interviews and a review of the literature in the field. The data from the field through the inductive analysis presented in planned stages. Data were sufficient when it could answer the research subject matter. These results of the research are the characteristic Jakarta’s residents in determining the political choice is very various, there are people who want to get involved in it directly, but also there are people who do not want to get involved.